Model Pembinaan Pencak Silat di Indonesia: Tinjauan Sistematis Literatur Tahun 2020-2025 - Brahmana Rangga Prastyana; Mohammad Furqon Hidayatullah; Slamet Riyadi; Hanik Liskustyawati (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aims to analyze the development of Pencak Silat coaching models in Indonesia for the 2020-2025 period through a systematic literature review. The research design employs a systematic review method following the PRISMA guidelines to ensure transparency and replicability of the process. Data sources and search strategy include scientific databases such as Google Scholar, Scopus, and SINTA, using keyword combinations like "pencak silat coaching model" and Boolean operators. A systematic article screening process was applied, starting from 106 identified records and proceeding through stages of deduplication, relevance screening, and a quality assessment using a scoring system, culminating in 18 final articles meeting the criteria. The data synthesis process involved extracting and thematically analyzing key information from the selected articles, such as objectives, methods, and findings. The results reveal that the research landscape remains dominated by fragmented, evaluative approaches, with infrastructure limitations, coach capacity, and non-technical aspects as primary challenges. The study concludes by emphasizing the urgent need to develop a holistic and contextually appropriate coaching model, supported by applicable policy frameworks for the sustainability of Pencak Silat development.